PPIs therapy has a negative impact on the clinical outcomes of advanced SCLC patients treated with PD-L1 inhibitors - Sisi Zhang; Jing Tian; Xinwei Wang; Chengxin Liu (BMC Pulmonary Medicine, 2023)
Abstract Background Programmed death-ligand 1 (PD-L1) inhibitors has emerged as a first-line therapeutic strategy for advanced small cell lung cancer (SCLC), which can stimulate T-cell activation, thereby preventing tumor avoidance of immunologic surveillance, whereas, proton pump inhibitors (PPIs) can play an important role in regulating immune function. This study assessed whether the concomitantly use of PPIs affected outcomes of immunotherapy in advanced SCLC. Methods Data from advanced SCLC patients who firstly treated with PD-L1 inhibitors between July 2018 and February 2021 was retrospectively analyzed. The impact of concomitant medications (especially PPIs) on objective response rate, progression-free survival (PFS) and overall survival (OS) were evaluated. Results Of 208 patients, 101 received immunotherapy concomitant PPIs. The median PFS of patients receiving PPIs (6.6 months) were significantly shorter than those without PPIs (10.6 months), and so was OS. There was associated with a 74.9% increased risk of progression and 58.3% increased risk of death. Both first-line and post-first-line immunotherapy, patients treated PPIs had poorer PFS. Conclusion PPIs therapy has a negative impact on the clinical outcomes of advanced SCLC patients treated with PD-L1 inhibitors.